IFLA Study on Functional Requirements of Bibliographic Records ant Its Significance for the National Bibliographic Services and Cataloguers - Osvaldas Janonis (Knygotyra)
The introduction to the article gives an account of the international co-operation in the sphere of cataloguing since 1954. AI present one of the most important problems is the price of the cataloguing process. The creation of a full bibliographic record by the national bibliographic services is an expensive activity. Therefore the idea of its simplification came into being. The attention was focused on the functionality of a bibliographic record. IFLA has organised a special research of this problem. The main goal of the article is to analyse the organisation and the results of the study from the point of view of its significance for national bibliographic services, cataloguers, and teachers of cataloguing disciplines.